Genome and Ontogenetic-Based Transcriptomic Analyses of the Flesh Fly, Sarcophaga bullata. Issue 5 (1st May 2019) - Martinson, Ellen O; Peyton, Justin; Kelkar, Yogeshwar D; Jennings, Emily C; Benoit, Joshua B; Werren, John H; Denlinger, David L
Abstract: The flesh fly, Sarcophaga bullata, is a widely-used model for examining the physiology of insect diapause, development, stress tolerance, neurobiology, and host-parasitoid interactions. Flies in this taxon are implicated in myiasis (larval infection of vertebrates) and feed on carrion, aspects that are important in forensic studies. Here we present the genome of S. bullata, along with developmental- and reproduction-based RNA-Seq analyses. We predict 15, 768 protein coding genes, identify orthology in relation to closely related flies, and establish sex and developmental-specific gene sets based on our RNA-Seq analyses. Genomic sequences, predicted genes, and sequencing data sets have been deposited at the National Center for Biotechnology Information. Our results provide groundwork for genomic studies that will expand the flesh fly's utility as a model system.